Personal Learning Letter Writing Model Using Exercise Technique Based on Curriculum 2006 KTSP - Nurwilah, Lilis Dewi; Sobari, Teti (JLER (Journal of Language Education Research), 2018)
The development of an educational curriculum is one part of educational reform. One of them is the competency-based curriculum. This curriculum emerges as an effort to perfect the learning strategy. This study refers to the Education Unit Level Curriculum. Therefore, the problem of this research is related to the learning system based on KTSP 2006. The research problem is limited to 3 aspects, namely (1) the preparation model of learning to write a personal letter; (2) the implementation of personal letter writing lessons with exercise techniques; (3) the result of a personal letter writing process. Furthermore, the authors also establish a hypothesis which reads: if the personalized vocabulary is taught by training techniques and in accordance with the syllabus and prepared learning plan, then the results will be satisfactory. "This method uses the description method, this method is used to describe the feasibility of learning by step (1) making a syllabus, (2) making a lesson plan, (3) asking teacher's judgment, 4) reconciling and interpreting from the teacher.From the result of analysis to teacher's appraisal, the conclusion of learning model writing personal letter writer the stack is widely used for grade IV elementary students.The feasibility of the learning model is based on the results of the teacher's assessment of the syllabus and the lesson plans and teaching and learning activities.